Glutathione–ROS pathway activation by probiotic B240 augments macrophage response to influenza - Ye, Zhen; Zhang, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEarly outcomes of influenza−induced lung injury depend on the rapid activation of the macrophage–type I interferon (IFN) axis, a process that requires tightly regulated glutathione–reactive oxygen species (GSH–ROS) buffering.ObjectiveThe aim of this study was to determine whether oral Lactobacillus pentosus B240 amplifies the macrophage–IFN response by pre−modulating the GSH–ROS pathway, thereby enhancing innate immunity against the H1N1 virus.MethodsThe public dataset GSE43764 (48 Agilent one−color microarrays) was re−analyzed using ComBat batch correction, limma differential analysis, gene set variation analysis (GSVA) functional scoring, weighted gene co-expression network analysis (WGCNA) co−expression, CIBERSORTx deconvolution, and mixed−effects modeling; all statistics were Benjamini–Hochberg adjusted.ResultsIn uninfected mice, pulmonary Gclc was significantly upregulated in the B240 group (padj < 0.05) and overall GSH–ROS and Nrf2 GSVA scores were higher than controls; after the viral challenge, GSH–ROS, Nrf2, macrophage activation, and type I IFN GSVA scores showed significant interactions from 1 to 6 days (q < 0.05). At 1 dpi, B240+CA04 versus Saline+CA04 had 418 upregulated and 289 downregulated genes (padj < 0.05, |log2FC| ≥ 0.58), dominated by macrophage markers and ISGs. Gclc and Nqo1 were elevated at 1–3 days (p < 0.05), and Adgre1 and Rsad2 were elevated at 1–6 days (p < 0.01). The WGCNA red module (312 genes) correlated most strongly with GSH–ROS GSVA and macrophage abundance (q < 0.05); GSH–ROS core genes (Gclc and Nqo1) and macrophage–IFN genes (Adgre1, Mx1, and Rsad2) were co−expressed (Pearson r > 0.2, FDR < 0.05). Enrichment covered viral response, type I IFN, RIG−I−like, Toll−like, NOD−like, and JAK−STAT antiviral pathways, plus GSH metabolism, oxidative stress, and macrophage activation (all q < 0.05). CIBERSORTx showed macrophage abundance and the M1/M2 index remained higher at 1, 3, and 6 dpi with B240, with three−way interaction estimates of 0.28 and 0.59 (q = 0.002). Single−sample analysis revealed stronger GSH–ROS versus macrophage–ISG correlation in B240 (r = 0.81, q = 0.001) than control (r = 0.53, q = 0.008); Fisher z padj = 0.015. Integrative network nodes had Spearman ρ 0.58–0.72 (q < 0.05), confirming oxidative–IFN coupling.ConclusionsB240 elevates baseline GSH–ROS thresholds and reshapes a red co−expression module, synchronously amplifying macrophage infiltration and type I IFN feedback, thereby strengthening early innate responses to H1N1 infection and suggesting nutritional–immunological prophylaxis for high−risk respiratory viral exposure.